Caracterização molecular de amostras de Toxoplasma gondii isoladas de animais natural e experimentalmente infectados e de amostras clínicas - Mariana Maciel Cunha (2014)
The isolation of Toxoplasma gondii by mouse bioassay is the most used method for molecular characterization of this parasite. Genotyping directly in biological samples can be a useful and fast tool, which allows the analysis of a large number of samples. The aim of this study was genotyping T. gondii from different biological samples using multiplex multilocus nested PCR-RFLP (Mn PCR-RFLP). Lung and brain of mice experimentally infected were used with five isolates of T. gondii, 15 heart samples from naturally infected free-range chickens as well as 12 human blood samples of newborns with congenital toxoplasmosis were used. The genotypes obtained were identified and compared with ToxoDB database (http://toxodb.org/toxo/). In experimentally infected mice, the complete genotype was obtained from DNA extracted from lungs after seven days of infection. In the brain, there was no amplification in most samples. The difference between the amplifications in the two organs may reflect the kinetics of dispersion and multiplication of the parasite and the pathogenic ability of different isolates. In naturally infected free-range chickens, it was possible to perform complete genotyping in two samples and partial genotyping in 13 samples. The two new genotypes obtained were not yet described in the literature. In blood from infants with congenital toxoplasmosis it was possible to perform partial genotyping of eight of the 12 samples analyzed.